Consciousness and the mind of God - Taliaferro, Charles (Cambridge [England] ; New York, NY, USA : Cambridge University Press, 1994)
Consciousness and the Mind of God is especially concerned with central metaphysical claims about the nature of persons and the implications of these claims for the philosophy of God. Charles Taliaferro shows that in the contemporary climate there is a widespread view that the insights gained from a philosophy of human persons lead either to a total abandonment of traditional theistic claims about God or to a radical revision of theistic claims about how God relates to the world. Thus, the preponderance of physicalism has led a wide range of philosophers and theologians to reconsider the traditional conception of God as a nonphysical person or person-like reality, ideas about the afterlife, and the Christian doctrine of the incarnation. Some have taken the plausibility of physicalism to be a sufficient ground for embracing philosophical atheism, and thereby rejecting wholesale the fundamental claims of Christianity, Judaism, and Islam. Others have taken the success of a physicalist philosophy to justify treating religion along noncognitive lines. Taliaferro critically examines these options, and defends a nonphysicalist understanding of the God-world relation. He maintains that, while persons are not identical with their bodies, and God is not identical with the cosmos, it remains the case that persons and bodies, God and the cosmos, "exist in a profoundly integral union." His notions of "integrative dualism" and "integrative theism" seek to avoid some of the extremes of Cartesian and Platonic dualism.
1. Consciousness -- 2. The material world -- 3. Persons and bodies -- 4. God and the world -- 5. The omnipresence of God -- 6. Integrative theism.
Includes bibliographical references (p. 342-345) and index.
Keywords: God -- Proof; Dualism; Materialism; Consciousness